Impacts of Climate Change on Dengue Risk in Brazil - Paula Carvalho Pereda; Tatiane Menezes; Denisard C. O Alves (Inter-American Development Bank (IDB), 2014)
Climate-sensitive health problems kill millions every year and undermine the physical and psychological well-being of millions more. To identify the climate impacts on dengue risk in Brazil, a comparative case study is used based on the synthetic controls approach. The South and Northeast regions of Brazil are compared to the rest of the country in order to identify those impacts. The results suggest that dengue is more prevalent in warmer regions, but the humidity conditions and amount of rainfall seem fundamental for increase of the diseases prevalence in temperate climate regions or drier tropical regions of the country. On the other hand, the increase in rainfall in the rainiest tropical areas could diminish the diseases prevalence, as standing water accumulations might be washed away. Therefore, due to expected climate changes in the future, the dengue fever distribution in the country might change, with the disease migrating from the north to the south. Public policy's role in minimizing these effects in the country should be focused on anticipating the proper climate conditions for dengue incidence by using integrated actions among local authorities.
hdl:11319/6566
Keywords: I18; Q54; 330; Dengue fever; Synthetic control method; Climate change impacts on health